Global Research Trends on Prostate Diseases and Erectile Dysfunction: A Bibliometric and Visualized Study - Ma, Chengquan; Su, Hao; Li, Hongjun (Frontiers in Oncology, 2021)
Objectives: To identify the cooperation of authors, countries, institutions and explore the hot topics prospects regarding research of prostate diseases and erectile dysfunction (ED). Methods: Publications on research of prostate diseases and ED were retrieved from the Web of Science Core Collection (WoSCC). Bibliometric analyses were performed using VOSviewer and CiteSpace software. Network maps were generated to evaluate the collaborations between different authors, countries, institutions and keywords. Results: A total of 2599 articles related to study of prostate diseases and ED were identified. We observed gradually increasing in the number of publications from 1998 to 2016, and the trend was to be relatively stable in the past three years. Journal of Sexual Medicine (243 papers) owned the highest number of publications and Journal of Urology was the most co-cited journal. Mulhall John P (52 papers) was the top most productive authors and Mcvary Kebin T with the largest numbers of citations (1589 co-citations) during the past decades. There were active collaborations among the top authors. The USA was the leading contributor in this field with 1078 papers. Active cooperation between countries and between institutions was observed. The main hot topics included matters related to erectile dysfunction, prostate cancer, quality-of-life, radical prpstatectomy, sexual function and BPH. Conclusion: Studies of prostate diseases and ED have gradually increasing after 1998 and were relatively stable in the past three years. The USA contributed the most publications. There were active cooperation between authors, countries, and institutions. Further research should expand and develop new topics such as treatment.